Skills acquisition in basic cardiopulmnar and resuscitation in a secondary school - Pérez Bailón, Ana María; Cárdenas Cruz, Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Cardiorespiratory arrest (CA) is one of the leading causes of death in industrialized countries. Performing cardiopulmonary resuscitation (CPR) by witnesses increases survival, however CPR training is not included in education in Spain. In this paper we analyze the implementation of a training program for Secondary Education teachers by healthcare professionals and subsequently the acquisition of skills by students, comparing according to the trainer who instructs them (teacher or healthcare provider), at Secondary Education centre in Granada (Spain), aiming at an adequate acquisition of global skills, being better when the trainer is a teacher.